2009
DOI: 10.1017/s0031182009990746
|View full text |Cite
|
Sign up to set email alerts
|

Flea infestation reduces the life span of the common vole

Abstract: Parasitism is often a source of variation in host's fitness components. Understanding and estimating its relative importance for fitness components of hosts is fundamental from physiological, ecological and evolutionary perspectives. Host-parasite studies have often reported parasite-induced reduction of host fecundity, whereas the effect of parasitism on host survival has been largely neglected. Here, we experimentally investigated the effect of infestation by rat fleas (Nosopsyllus fasciatus) on the life spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Interestingly, such accelerated growth did not come at the expense of resistance to oxidative stress as expected under the growth vs. self‐maintenance resource allocation trade‐off (Stearns, ; Metcalfe & Monaghan, ; Dmitriew, ), and as shown by some empirical studies (Alonso‐Alvarez et al ., ; Hall et al ., ). In fact, both of our oxidative stress markers remained unaffected by the flea infestation, a pattern also observed in other species (Devevey & Christe, ; Mougeot et al ., ), possibly highlighting the complexity of the interplay among oxidative stress, growth and immunity. Because a direct activation of the immune system generally increases oxidative stress (Costantini & Møller, ), our results might indicate that animals evolved physiological strategies to cope with parasite infestations without compromising their resistance to oxidative stress.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, such accelerated growth did not come at the expense of resistance to oxidative stress as expected under the growth vs. self‐maintenance resource allocation trade‐off (Stearns, ; Metcalfe & Monaghan, ; Dmitriew, ), and as shown by some empirical studies (Alonso‐Alvarez et al ., ; Hall et al ., ). In fact, both of our oxidative stress markers remained unaffected by the flea infestation, a pattern also observed in other species (Devevey & Christe, ; Mougeot et al ., ), possibly highlighting the complexity of the interplay among oxidative stress, growth and immunity. Because a direct activation of the immune system generally increases oxidative stress (Costantini & Møller, ), our results might indicate that animals evolved physiological strategies to cope with parasite infestations without compromising their resistance to oxidative stress.…”
Section: Discussionsupporting
confidence: 87%
“…v www.esajournals.org There is growing evidence that ectoparasites can have significant negative impacts on the physiology of individual hosts, and the vital rates of host populations (Hawlena et al 2006a, Hawlena et al 2006b, Devevey et al 2008, Devevey and Christe 2009, Pfäffle et al 2009, Kam et al 2010. Therefore, it is conceivable that lowered ectoparasite loads in burned forest contribute to high post-fire deer mouse abundance, e.g., through effects on body condition (Hawlena et al 2006a, Devevey et al 2008, Devevey and Christe 2009 or feeding behavior (Scantlebury et al 2007, Raveh et al 2011), which in turn influences reproductive output of deer mice. Intriguingly, Raveh et al (2011) showed that flea-infested rodents were less vigilant and v www.esajournals.org had higher giving-up densities (i.e., tended to quit foraging at higher densities of food remaining in the patch).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are multiple studies demonstrating individual-level impacts of ectoparasites on hosts, with most research conducted on fleas. In laboratory studies, fleas were found to affect body condition, growth rate, life span, and energy expenditure of their hosts (e.g., Hawlena et al 2006a, Devevey et al 2008, Devevey and Christe 2009. In free-living animals, ectoparasites influenced host energy budgets (Giorgi et al 2001, Nilsson 2003, Kam et al 2010, litter size (Neuhaus 2003), foraging and vigilance patterns (Scantlebury et al 2007, Raveh et al 2011, and juvenile survival (Hawlena et al 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental work in natural populations, where individuals are treated to remove parasites and compared with untreated individuals, has typically shown that parasite‐free individuals show higher survival or reproductive success (e.g. Devevey & Christe, 2009; Knowles et al. , 2010).…”
Section: Introductionmentioning
confidence: 99%